Global occurrence of the bacteria with capability for extracellular reduction of iodate - Guo, Jinzhi; Jiang, Jie; Peng, Zhaofeng; Zhong, Yuhong; Jiang, Yongguang; Jiang, Zhou; Hu, Yidan; Dong, Yiran; Shi, Liang (Frontiers in Microbiology, 2022)
The γ-proteobacterium Shewanella oneidensis MR-1 reduces iodate to iodide extracellularly. Both dmsEFAB and mtrCAB gene clusters are involved in extracellular reduction of iodate by S. oneidensis MR-1. DmsEFAB reduces iodate to hypoiodous acid and hydrogen peroxide (H2O2). Subsequently, H2O2 is reduced by MtrCAB to facilitate DmsEFAB-mediated extracellular reduction of iodate. To investigate the distribution of bacteria with the capability for extracellular reduction of iodate, bacterial genomes were systematically searched for both dmsEFAB and mtrCAB gene clusters. The dmsEFAB and mtrCAB gene clusters were found in three Ferrimonas and twenty-six Shewanella species. Coexistence of both dmsEFAB and mtrCAB gene clusters in these bacteria suggest their potentials for extracellular reduction of iodate. Further analyses demonstrated that these bacteria were isolated from a variety of ecosystems, including the lakes, rivers and subsurface rocks in East and Southeast Asia, North Africa and North America. Importantly, most of the bacteria with both dmsEFAB and mtrCAB gene clusters were found in different marine environments, which ranged from Artic Ocean to Antarctic coastal marine environments as well as from Atlantic Ocean to Indian and Pacific Oceans. Widespread distribution of the bacteria with capability for extracellular reduction of iodate around the world suggests their significant importance in global biogeochemical cycling of iodine. The genetic organization of dmsEFAB and mtrCAB gene clusters also varied substantially. The identified mtrCAB gene clusters often contained additional genes for multiheme c-type cytochromes. The numbers of dmsEFAB gene cluster detected in a given bacterial genome ranged from one to six. In latter, duplications of dmsEFAB gene clusters occurred. These results suggest different paths for these bacteria to acquire their capability for extracellular reduction of iodate.